Investigation of the reliability of computing systems - Trushakov, Dmitro; Moshna, Dmitro (Видавництво Львівської політехніки, 2011)
In the article is described the investigation of the reliability of computing system – personal computer and also specific computing machine which is charged to solve problems and tasks of various complication and have to suit the level of reliability, for example, for such implementation as constructing and production in mechanical engineering.
Keywords: personal computer; reliability; operating time; failure